Predation of portunid crabs Callinectes sapidus and Callinectes ornatus (Crustacea, Decapoda) on the medusa Lychnorhiza lucerna (Cnidaria, Scyphozoa) (Ocean and Coastal Research, 2024)
Predation of portunid crabs Callinectes sapidus and Callinectes ornatus (Crustacea, Decapoda)